'It's so beneficial to be able to stop the cycle': perceptions of intergenerational transmission of violence and parenting practices among pregnant women and their abusive partners - Taccini, Federica (Journal of family violence, 2025)
Purpose: This study aimed to explore how pregnant women who experience Domestic Violence and Abuse (DVA) and men who commit DVA understand the impact of their childhood environment on their relationships with their children and co-parents, and how a DVA psychological intervention may shape their parenting. Methods: Repeated individual qualitative interviews were conducted with pregnant mothers and fathers who reported DVA and were taking part in a psychological intervention to address DVA. Interviews were carried out at the start (during pregnancy) and end of the intervention (two years post-childbirth). Reflexive Thematic Analysis was used to analyse interviews. Results: 56 interviews (26 mothers; 13 fathers) were analysed. Five themes were identified: (1) Acknowledging childhood experiences of DVA; (2) The scars of traumatic experiences; (3) Challenging the silencing of abuse; (4) The transmission of parenting styles and behaviours from one generation to another; (5) Becoming the best parent one can be. The intergenerational transmission of violence was identifiable in most narratives. Despite this, several participants described skills they acquired during the intervention (e.g., emotional regulation strategies) as assisting in interrupting violence and improving their relationships with their children. Conclusions: Participants who acknowledged having encountered childhood abuse recognised it as one of several risk factors for DVA in adulthood. They also discussed the potential for trauma-informed interventions to address the intergenerational transmission of violence and poor parenting practices.